2005
DOI: 10.1103/physrevb.71.125306
|View full text |Cite
|
Sign up to set email alerts
|

Defective transport properties of three-terminal carbon nanotube junctions

Abstract: We investigate the transport properties of three terminal carbon based nanojunctions within the scattering matrix approach. The stability of such junctions is subordinated to the presence of nonhexagonal arrangements in the molecular network. Such "defective" arrangements do influence the resulting quantum transport observables, as a consequence of the possibility of acting as pinning centers of the correspondent wavefunction. By investigating a fairly wide class of junctions we have found regular mutual depen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 57 publications
0
18
0
1
Order By: Relevance
“…The treatment of these models can be distinguished according to the level at which interaction is taken into account. Here, we are in particular interested in two situations in which the many-body problem can be traced back to the dynamics of single electrons on the wire: The first case premises non-interacting electrons for which the current can be computed from a Landauer-like formula [15][16][17][18][19][20]. The second case deals with the opposite limit in which Coulomb repulsion is so strong that at most one excess electron can be located on the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of these models can be distinguished according to the level at which interaction is taken into account. Here, we are in particular interested in two situations in which the many-body problem can be traced back to the dynamics of single electrons on the wire: The first case premises non-interacting electrons for which the current can be computed from a Landauer-like formula [15][16][17][18][19][20]. The second case deals with the opposite limit in which Coulomb repulsion is so strong that at most one excess electron can be located on the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…To deal with such semi-infinite leads, we adopt a recursive renormalization procedure already described in Ref. 23. Considering the leads as bulk gold will yield an increased imaginary part of the lead self-energies, which will slightly decrease the conductance values.…”
Section: Methodsmentioning
confidence: 99%
“…Carbon nanotube ͑CNT͒ multiterminal junctions ͑MTJs͒ with T, Y, and X shapes are excellent candidates for nanoscale electronic devices due to their superior combination of electronic and mechanical properties, as well as their inherent nanosize. [1][2][3][4][5][6][7][8][9] Significant efforts have been devoted to understanding and characterizing properties of single-walled nanotube ͑SWNT͒ MTJs, and their production and application. The thermal conductivity of nanometer materials plays a fundamentally critical role in controlling the performance and stability of nano-/microdevices, since a significant amount of heat may need to be dissipated from the nano-/microdevices to prevent structural damages.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and theoretical studies [3][4][5][6][7] have shown that both the symmetry of the Y junction and the chirality of the trunk and branches play a role in the rectification behavior of these structures, with the symmetry being a more significant factor. It is therefore important to know how the topological defects influence the thermal conduction properties of CNTs.…”
Section: Introductionmentioning
confidence: 99%